Searching on the Campus? Marriage Market Effects of the Student Gender Composition by Field of Study - Nico Pestel (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper examines the effect of the student sex ratio on marriage market outcomes of university graduates in Germany. Using Microcensus data combined with administrative information on the gender composition of students, I exploit substantial variation in gender imbalances by field of study experienced by individuals holding a tertiary degree at the time of education. The main findings show that a higher share of the own gender among fellow students negatively affects marriage market opportunities for women and significantly decreases the probability of living with a partner from the same field for both men and women. Moreover, when the own gender is abundant men are more likely to marry down with respect to educational status, while women rather have a partner with the same level of education.
Keywords: D10; I24; J12; 330